(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This paper explores the complex relationship between the subject and its roles in syntactics and semantics within linguistic frameworks. We investigate how the subject, as both a syntactic entity and a semantic role, affects sentence structure and meaning. Through a detailed analysis of syntax, where sentences are formed by rules and principles, and semantics, where meanings are constructed from the interaction of linguistic parts, this study highlights the interdependent nature of syntax and semantics. The paper emphasizes the subject’s pivotal role in interpreting ambiguity, imposing syntactic constraints, and influencing semantic roles across various languages and contexts. This exploration contributes to a deeper understanding of linguistic theory and its applications in computational linguistics, providing insights into how language processes and generates human-like text.